The Ideas Of Independence In The Satirical Prose of Abdurrahim Bey Ahverdiev (Eurasian Journal of Philology Science and Education, 2016)
Satirical stories and satires one stands out for its individual style masters Abdurrahim Bey Ahverdiev in the history of fiction has a special place. This article written by him have been investigated in the early twentieth century, the same type of art works. In the satirical skits and stories reflected the open and hidden call to the writer’s struggle for national independence, a categorical protest against the violation of the rights of our people. The rebel attitude to the Tsarist Russia and the Soviet regime, support the constitutional movement in Iran are the basis of the involved study material. The author investigates mainly works «The letters from hell», «MyDeer» e.a, in which his usual subtlety, a hint of concerns and questions call for the ideals of independence, national unity, free Azerbaijani man.
Keywords: historical fiction; the idea of independence; a magazine «Molla Nasreddin»